Effects of seawater pH and temperature on foraging behavior of the Japanese stone crab Charybdis japonica. Issue 1 (15th July 2017) - Wu, Fangli; Wang, Ting; Cui, Shuaikang; Xie, Zhe; Dupont, Sam; Zeng, Jiangning; Gu, Huaxin; Kong, Hui; Hu, Menghong; Lu, Weiqun; Wang, Youji
Abstract: We examined prey selection and foraging behaviors of the crab Charybdis japonica exposed to four combinations of pH (7.3 and 8.1) and temperature (18 °C and 25 °C). The order of prey selection by C. japonica was Potamocorbula laevis, Ruditapes philippinarum, Tegillarca granosa and Mactra veneriformis . Under high pCO2, times for searching, breaking, eating and handling were all significantly longer than those at the normal pCO2, and the prey profitability and predation rate under high pCO2 were significantly lower than normal pCO2 . Moreover, temperature significantly influenced the foraging behaviors, but its effects were not as strong as those of pH; times for searching, eating and handling under high temperature were significantly lower than the low temperature, and the prey predation rates under high temperature was significantly higher than low temperature. In conclusion, high pCO2 negatively affected the foraging behavior, but high temperature actively stimulated the foraging behaviors of crabs. Graphical abstract: Highlights: Prey selection and foraging behaviors of Charybdis japonica were examined. Neither pH nor temperature had a significant effect on the prey preference. Low pH significantly increased the time for foraging and feeding of crabs. High temperature significantly increased the foraging behaviors of crabs. Temperature and pH had opposite effects on the crab foraging behavior.